Density Functional Theory-Based Studies Predict Carbon Nanotubes as Effective Mycolactone Inhibitors - Nafiu Suleiman; Abu Yaya; Michael D. Wilson; Solomon Aryee; Samuel K. Kwofie (Molecules, 2022)
Fullerenes, boron nitride nanotubes (BNNTs), and carbon nanotubes (CNTs) have all been extensively explored for biomedical purposes. This work describes the use of BNNTs and CNTs as mycolactone inhibitors. Density functional theory (DFT) has been used to investigate the chemical properties and interaction mechanisms of mycolactone with armchair BNNTs (5,5) and armchair CNTs (5,5). By examining the optimized structure and interaction energy, the intermolecular interactions between mycolactone and nanotubes were investigated. The findings indicate that mycolactone can be physically adsorbed on armchair CNTs in a stable condition, implying that armchair CNTs can be potential inhibitors of mycolactone. According to DOS plots and HOMO–LUMO orbital studies, the electronic characteristics of pure CNTs are not modified following mycolactone adsorption on the nanotubes. Because of mycolactone’s large π-π interactions with CNTs, the estimated interaction energies indicate that mycolactone adsorption on CNTs is preferable to that on BNNTs. CNTs can be explored as potentially excellent inhibitors of mycolactone toxins in biological systems.